The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s1519-70772004000300005
|View full text |Cite
|
Sign up to set email alerts
|

A informação contabilística nas decisões financeiras das pequenas empresas

Abstract: O presente artigo tem por objectivo analisar a importância da informação contabilística atribuída pelos empresários/gestores das pequenas empresas na tomada de decisão estratégica (que comporta as decisões de investimento, financiamento e distribuição de dividendos) e operacional (relacionada com as decisões de gestão corrente). Assim como, verificar se existem grupos distintos de empresas na importância atribuída à informação contabilística segundo as decisões estratégicas e operacionais e se esses grupos se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 16 publications
0
3
1
4
Order By: Relevance
“…By Bezerra (2012) most of the financial information provided by the accounting does not have any association with the place where it is prepared. However, these results aren't in line with those presented by Nunes and Serrasqueiro (2004), who concluded that there is a positive association between the place and the importance given to financial information because business owners/managers tend to give greater importance to the financial information when it is prepared in the company's infrastructure (inside the company). In this respect also Santos (2014) came to argue that the financial information is prepared in the company's infrastructure tends to respond better to the needs of its users, including administrators/managers, which Bezerra (2012) reinforces, saying that when companies have a professional to prepare the financial information in the company's infrastructure tend to better understand its importance and usefulness to the decision-making process.…”
Section: Research Hypotheses Variables P-valuecontrasting
confidence: 70%
See 1 more Smart Citation
“…By Bezerra (2012) most of the financial information provided by the accounting does not have any association with the place where it is prepared. However, these results aren't in line with those presented by Nunes and Serrasqueiro (2004), who concluded that there is a positive association between the place and the importance given to financial information because business owners/managers tend to give greater importance to the financial information when it is prepared in the company's infrastructure (inside the company). In this respect also Santos (2014) came to argue that the financial information is prepared in the company's infrastructure tends to respond better to the needs of its users, including administrators/managers, which Bezerra (2012) reinforces, saying that when companies have a professional to prepare the financial information in the company's infrastructure tend to better understand its importance and usefulness to the decision-making process.…”
Section: Research Hypotheses Variables P-valuecontrasting
confidence: 70%
“…This issue is still undeveloped, not if sufficiently knowing which is the importance attributed by such companies to the financial information. The majority of the studies that have study the importance of the financial information was focused on the companies of a general form (e.g., Lima, 2000;Passos, 2010), on companies of a certain activity sector (e.g., Alves, 2005), or on companies of a certain size and/or location (e.g., Abatti, 2004;Bezerra, 2012;Laureano, 2006;Nunes & Serrasqueiro, 2004;Santos, 2012;Stroeher & Freitas, 2008). In this case, the preponderance of these enterprises in the national economy and the lack of results on the importance that they assigned to the financial information are the basis of this study, that aims determine the role and importance that accounting assumes in the decision-making process in these companies.…”
Section: Introductionmentioning
confidence: 99%
“…O contador tem elevado potencial de atuar na assessoria aos gestores das MPME, orientando-os na tomada de decisões (BIANCHI; BIVONA, 1999;MIRANDA et al, 2008). A despeito disso, diversas pesquisas têm evidenciado a baixa oferta de Contabilidade Gerencial para as MPME (MARRIOT; MARRIOTT, 2000;OLIVEIRA et al, 2000;SALGADO et al, 2000;SILVA, 2002;CALLADO et al, 2003;LIMA et al, 2004;NUNES;SERRASQUEIRO, 2004;STROEHER;FREITAS, 2006;CANECA, 2008;UMBELINO, 2008). Por outro lado, algumas pesquisas têm constatado que os gestores de MPME não só precisam receber informações gerencias como também estariam dispostos a pagar mais por elas (LEITE, 2004;UMBELINO, 2008;CANECA, 2008;MIRANDA et al, 2008).…”
Section: A Importância Da Contabilidade Gerencial Para As Mpmeunclassified
“…Este estudo tem como foco os serviços de consultoria sobre práticas gerenciais voltadas para as micro, pequenas e médias Empresas (MPME). Este conjunto de empresas representa parcela predominante do total de empresas, não só no Brasil, como também em outros países (STOREY, 1994; BAARD; VAN DEN BERG, 2004;NUNES;SERRASQUEIRO, 2004;RIGBY, 2011). A literatura mostra que a falta de conhecimento gerencial dos gestores na administração dos negócios constitui-se como uma das principais causas para o encerramento das atividades das micro, pequenas e médias empresas (HOLMES; HASWELL, 1989;SILVA, 2002;CERQUEIRA;AZEVEDO, 2004;OLEIRO;DAMEDA, 2005;STROEHER, 2006;RIGBY, 2011;SEBRAE, 2004aSEBRAE, , 2004bSEBRAE, , 2005bSEBRAE, , 2008SEBRAE, , 2010.…”
Section: Introductionunclassified
See 1 more Smart Citation